The Eighteenth Centuries : Global Networks of Enlightenment - Wall, Cynthia, 1959-; Gies, David T. (Book collections on Project MUSE., 2018)
Today, when "globalization" is a buzzword invoked in nearly every realm, we turn back to the eighteenth century and witness the inherent globalization of its desires and, at times, its accomplishments. During the chronological eighteenth century, learning and knowledge were intimately connected across disciplinary and geographical boundaries, yet the connections themselves are largely unstudied. In The Eighteenth Centuries, twenty-two scholars across disciplines address the idea of plural Enlightenments and a global eighteenth century, transcending the demarcations that long limited our grasp of the period's breadth and depth. Engaging concepts that span divisions of chronology and continent, these essays address topics ranging from mechanist biology, painted geographies, and revolutionary opera to Americanization, theatrical subversion of marriage, and plantation architecture. Weaving together many disparate threads of the historical tapestry we call the Enlightenment, this volume illuminates our understanding of the interconnectedness of the eighteenth centuries.